Polymorphisms of the GSTM1 and GSTT1 genes in patients with allergic diseases in the Czech population - Holla, L I; Stejskalova, A; Vasku, A (Allergy, 2006)
BACKGROUND: Allergic diseases belong to the most common chronic disorders affecting mankind and their prevalence in population is increasing. Several studies have indicated that oxidative stress impairs pulmonary function and makes existing asthma worse. Members of the glutathione-S-transferase (GST) superfamily of genes are important in protection of cells from reactive oxygen species. AIMS OF THE STUDY: Relationships among allergic diseases including asthma and variations in the GST mu (GSTM1) and GST theta (GSTT1) genes were investigated in 1,006 Caucasian subjects. METHODS: The multiplex polymerase chain reaction protocol was used for simultaneous amplification of both genes for molecular analysis. Genotype frequencies among patients and controls were assessed and the associations of the genotypes with intermediary phenotypes of allergy were statistically determined. RESULTS: The frequencies of GST null genotypes did not differ significantly between patients with allergic diseases (or asthma alone) and healthy controls. However, when compared with patients homozygous or heterozygous for GSTM1 functional allele, asthmatics carrying both GSTM1 null alleles displayed significantly worse lung function, assessed by forced expiratory volume in 1 s/forced vital capacity (FEV(1)/FVC) ratio (Tiffenau index), (P < 0.01). CONCLUSIONS: Genetic polymorphisms of the GSTM1 and GSTT1 genes, both individually and in combination, were not associated with the development of allergic diseases including asthma in the Czech population, the GSTM1 gene variability, however, may influence lung functions in our asthmatics.
Keywords: Genetic Predisposition to Disease; genotyp; alergie; Genotype; Česká republika; glutathiontransferasa; mužské pohlaví; Adult; Czech Republic; polymorfismus genetický; bronchiální astma; Glutathione Transferase; Polymorphism, Genetic; ženské pohlaví; Asthma; Humans; frekvence genu; Gene Frequency; dospělí; genetická predispozice k nemoci; Female; lidé; Male; Hypersensitivity